Lysoenzimuria as an indicator for lysosomal dysfunction of the proximal renal tubules in systemic lupus erythematosus treated with chloroquine phosphate - Spasovski, Dejan; Sandevska, Emilija; Pivkova Veljanovska, Aleksandra; Shubeska Stratrova, Slavica; Brezovska Kavrakova, Julijana (Macedonian Association of Anatomists and Morphologists, 2021)
Introduction: The approach for estimation of drug nephrotoxicity is possible only with drugs that have dominant proximal tubular excretion, such as methotrexate, chloroquine phosphate, diclophenum, acetaminophen. Very often, therapeutic drugs can have some nephrotoxic effect. This can be seen in a long-term SLE therapy. Aim: To estimate the effect of initial therapy with chloroquine phosphate and some most used nonsteroidal anti-inflammatory drugs (diclophenum) on tubular and glomerular function in patients with systemic lupus erythematosus (SLE), to determinate toxicity of these medicals through measurements of the urine enzyme excretion that correlates with the damage degree on the tubular epithelium. Microalbuminuria is used as a marker for glomerular damage, and the urinary excretion of N-Acetyl-b-D-glucosaminidase (NAG) as an indicator of proximal tubular damage. Material and methods: Using the colorimetric method for determination of NAG, as well as immunoturbidimetric assay for detection of microalbuminuria, we examined samples of 70 patients (35 SLE pts treated only with chloroquine phosphate, 35 SLE pts treated with diclophenum), followed up at five-time intervals within the course of 12 weeks. Results: There was a weak correlation between NAG and microalbuminuria (r=0.16) in the group of patients treated with chloroquine phosphate, while in the group treated with diclophenum, there was a moderate correlation (r=0.28). NAG enzymuria appeared earlier in the group treated with Diclophenum compared to the group treated with chloroquine phosphate. Conclusions: Diclophenum triggers greater tubular enzymuria than chloroquine phosphate.
Keywords: N-acetyl-b-D-glucosaminidase; microalbumin; systemic lupus erythematosus; chloroquine phosphate; diclophenum